Uncommon Coetaneous Histopathological Findings in Radicular Cyst: A Case Report - Keshwar, Shashi; Shrestha, Ashish; Shrestha, Sushmita; Raut, Tonia (Birat Journal of Health Sciences, 2020)
Radicular cyst is the most common inflammatory cyst of jaw. It arises from the epithelial residues in the periodontal ligaments as a result of pulp infection. Histopathologically radicular cyst lining reveals stratified squamous epithelium with arcade like pattern in early cases or quiescent epithelial lining in long standing cases. The wall of the radicular cyst is fibrous with mixed inflammatory cells infiltrate like neutrophils, plasma cells, lymphocytes and macrophages. There are very few reported cases of juxtaepithelial hyalinization of radicular cyst. Here we report a case of radicular cyst of a 28 year old male who presented with pus discharge from anterior right maxillary region. The cyst was associated with atrophic and tenuous epithelial lining with juxtaepithelial hyalinization along with focal Russell bodies. These findings are uncommoncoeval features of radicular cyst.